1994
DOI: 10.1021/ac00091a004
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Calcium Content in Individual Biological Cells by Inductively Coupled Plasma Atomic Emission Spectrometry

Abstract: A cell analyzer is described which can continuously determine the calcium content in individual biological cells by inductively coupled plasma atomic emission spectrometry in real time. A cell suspension in ethanol (70% in water) is sprayed by a concentric nebulizer, and the droplets containing ceils are dried in a drying chamber. The dried cells dispersed in air are directly introduced into the plasma to determine the calcium by emission spectrometry. Each flash derived from each cell in the plasma is convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 7 publications
0
48
0
Order By: Relevance
“…In recent years, single-cell elemental analysis using ICP-OES and ICP-MS has gained substantial interest in the biochemical and metallomics fields. 1,4,[7][8][9][10][11][12] If a suspension of cells can be directly introduced into the plasma as an aerosol, detailed information regarding the distribution of elements within a sample of cells can be obtained. There are many possible applications of this, such as simply comparing phosphorus levels in biological cells to give the distribution of cell size in a sample.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, single-cell elemental analysis using ICP-OES and ICP-MS has gained substantial interest in the biochemical and metallomics fields. 1,4,[7][8][9][10][11][12] If a suspension of cells can be directly introduced into the plasma as an aerosol, detailed information regarding the distribution of elements within a sample of cells can be obtained. There are many possible applications of this, such as simply comparing phosphorus levels in biological cells to give the distribution of cell size in a sample.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional systems have poor sample transport efficiencies to the plasma, typically <1% as previously noted. 7,9 One of the first articles on single cell introduction into ICP spectrometry was in 1994 by Nomizu et al, introducing mammalian cells (diameter 10 -20 μm) into ICP-OES to determine their calcium content. 7 It was found that introduction of the cells in solution was not feasible, due to large losses of cells from deposition on the apparatus, resulting in no signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elemental analysis of individual mammalian cells by time-resolved ICP-OES was first reported in 1994 by Nomizu et al 38 Calcium signals were successfully measured corresponding to individual cells; however, other elements, such as Mg, K and Na, could not be measured due to their insufficient detection limits. In the past decade, Li et al applied time-resolved ICP-MS to investigate the behavior of uranium compound-exposed bacteria in the ICP.…”
Section: Special Reviewsmentioning
confidence: 99%
“…There are several analytical methods for detecting Al 3+ such as atomic absorbance/emission spectroscopy, 16 inductively coupled plasma-mass spectroscopy (ICP-MS), 17 voltammetry, 18 electron paramagnetic resonance (EPR), 19 and high performance liquid chromatography. 20 Most of these methods require complicated samplepretreatment procedures, sophisticated synthetic procedures, and high operation costs.…”
Section: Introductionmentioning
confidence: 99%